Assessment of the hygrothermal air conditions of the science museum of the University of Coimbra - Pereira, Luísa Dias (2017)
This paper presents the preliminary results of the study of the hygrothermal air conditions of the Science Museum of the University of Coimbra (UC), a XVI-XVIII century building. It is located in the historic centre of the UC, officially declared as a World Heritage in 2013 by UNESCO. Since then, the museum has been receiving an increasing number of visitors. No previous studies on the environmental conditions of this museum were performed before. In face of this, the Rectorate of the University, who is concerned about the heritage preservation, started a research project focused on the thorough characterization of the hygrothermal air conditions within several museum rooms and on the assessment of risk situations, for both the heritage and human health issues. Within this paper, some early results of more than one-year monitoring of the hygrothermal air conditions of two exhibition rooms of the Museum are presented and discussed.